THE ROLE OF JOB SATISFACTION ON THE PERFORMANCE OF EDUCATIONAL STAFF - Dewi, Nurmila (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
This study aims to analyze the effect of compensation and leadership on the performance of educational staff with job satisfaction as a mediating variable at Lhokseumawe State Polytechnic. The approach used was quantitative with a survey method through questionnaires. A total of 85 educational staff members were selected proportionally and randomly from a total population of 155 employees. Data analysis was conducted using multiple linear regression assisted by SPSS software. The results showed that compensation and leadership had a positive and significant effect on job satisfaction. However, compensation and leadership did not directly affect the performance of educational staff. Meanwhile, job satisfaction was found to have a positive and significant effect on performance. The mediation test proved that job satisfaction fully mediated the relationship between compensation and leadership on performance. These findings emphasize the strategic role of job satisfaction in encouraging the improvement of educational staff performance within vocational higher education institutions.